COOPETITION AS A WAY OF IMPROVING STRATEGIC MANAGEMENT - Ільницький, Віталій (SWorldJournal, 2023)
The article shows that the latest trends show that the struggle in the markets is not for their share, but for intellectual leadership. The new paradigm for a company is to be able to identify its competitive advantages and develop its core competencies.